Questionable evidence for prospective effects of self-compassion and burnout on spiritual wellbeing: a simulated reanalysis and comment on Lee and Fung (2024) - Sorjonen, Kimmo; Melin, Bo (Frontiers in Psychology, 2025)
ObjectivesThe objective of the present simulated reanalysis was to scrutinize Lee and Fung's conclusion that self-compassion and burnout have causal effects on spiritual wellbeing.MethodologyWe simulated data to resemble the data used by Lee and Fung. We used triangulation and fitted complementary models to the simulated data.FindingsWe found contradictory increasing, decreasing, and null effects of initial self-compassion and burnout on subsequent change in spiritual wellbeing.ConclusionThe present divergent findings indicated that it is premature to assume causal effects of self-compassion and burnout on spiritual wellbeing and the suggestions by Lee and Fung in this regard can be challenged.ImplicationsIt is important for researchers to be aware that correlations, including adjusted cross-lagged effects, do not prove causality in order not to overinterpret findings, something that appears to have happened to Lee and Fung. We recommend researchers to triangulate by fitting complementary models to their data in order to evaluate if observed effects may be due to true causal effects or if they appear to be spurious.